Solar-driven electrochemical synthesis of ammonia using nitrate with 11% solar-to-fuel efficiency at ambient conditions. Issue 12 (7th September 2021) - Kani, Nishithan C.; Gauthier, Joseph A.; Prajapati, Aditya; Edgington, Jane; Bordawekar, Isha; Shields, Windom; Shields, Mitchell; Seitz, Linsey C.; Singh, Aayush R.; Singh, Meenesh R.
Abstract : An illustration of solar-driven synthesis of ammonia using nitrates with >10% solar-to-fuel efficiencies that can potentially decarbonize and decentralize ammonia production. Abstract : Ammonia is an essential commodity chemical used in the manufacture of fertilizers, pharmaceuticals, ammunition, and plastics, and is a promising alternative fuel source and carrier. Today most ammonia is manufactured by the century-old Haber–Bosch process, which accounts for 1–2% of worldwide energy production and a substantial fraction of global greenhouse gas emissions. Solar-driven electrochemical synthesis of ammonia using nitrates presents a sustainable pathway to produce renewable fuels utilizing wastewater. Previous efforts in solar-driven electrosynthesis of ammonia have been seriously affected by lower specific activity (<10 mA cm −2 ) of electrochemical nitrate reduction reaction (NiRR) and thereby lower solar-to-fuel (STF) efficiency (<1%). Here, we show oxide-derived Co as an efficient NiRR catalyst with the highest specific activity (∼14.56 mA cm −2 at −0.8 V vs. RHE) and selectivity. The oxide-derived Co offers a maximum faradaic efficiency of 92.37 ± 6.7% and ammonia current density of 565.26 mA cm −2 at −0.8 V vs. RHE. Integrating this catalyst in a PV-electrolyzer cell yields an unprecedented STF efficiency of 11% for ammonia, which is an order of magnitude higher than state-of-the-art systems.